Integrating GC-MS and comparative transcriptome analysis reveals that TsERF66 promotes the biosynthesis of caryophyllene in Toona sinensis tender leaves - Dai, Jianhua; Wang, Minyan; Yin, Hengfu; Han, Xiaojiao; Fan, Yanru; Wei, Yi; Lin, Jie; Liu, Jun (Frontiers in Plant Science, 2024)
The strong aromatic characteristics of the tender leaves of Toona sinensis determine their quality and economic value. Here, GC-MS analysis revealed that caryophyllene is a key volatile compound in the tender leaves of two different T. sinensis varieties, however, the transcriptional mechanisms controlling its gene expression are unknown. Comparative transcriptome analysis revealed significant enrichment of terpenoid synthesis pathway genes, suggesting that the regulation of terpenoid synthesis-related gene expression is an important factor leading to differences in aroma between the two varieties. Further analysis of expression levels and genetic evolution revealed that TsTPS18 is a caryophyllene synthase, which was confirmed by transient overexpression in T. sinensis and Nicotiana benthamiana leaves. Furthermore, we screened an AP2/ERF transcriptional factor ERF-IX member, TsERF66, for the potential regulation of caryophyllene synthesis. The TsERF66 had a similar expression trend to that of TsTPS18 and was highly expressed in high-aroma varieties and tender leaves. Exogenous spraying of MeJA also induced the expression of TsERF66 and TsTPS18 and promoted the biosynthesis of caryophyllene. Transient overexpression of TsERF66 in T. sinensis significantly promoted TsTPS18 expression and caryophyllene biosynthesis. Our results showed that TsERF66 promoted the expression of TsTPS18 and the biosynthesis of caryophyllene in T. sinensis leaves, providing a strategy for improving the aroma of tender leaves.